2014
DOI: 10.4236/health.2014.621345
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on Relationship between Test Anxiety and Academic Performance of Nursing and Midwifery Students in Tabriz and Maragheh—Iran

Abstract: Background and Aim: Given the dramatic decline in the ability of test due to test anxiety, the goal of this study was to evaluate the relationship between test anxiety and academic performances in students. Materials and Methods: This descriptive-analytical study was performed on 216 Iranian nursing and midwifery students in 2011-2012, utilizing Sarason Anxiety Inventory, demographic checklist and the average mark of students in the period of midterm and final exam. Multinomial logistic regression analyses by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Objective structured clinical examinations (OSCEs) are commonly included in health education curricula as they can be used to assess practical skill level and competency through simulation of a real world scenario, but in a mock clinical and examinable setting. Accordingly, OSCEs have been integrated into the curriculum for Bachelor of Nursing programs with other relevant forms of assessment, both internationally and within Australia (Alizadeh et al, 2014;Chiou-Rong & Ue-Lin, 2015;Jo & An, 2014;Mitchell, Henderson, Groves, Dalton, & Nulty, 2009;Setyonugroho, Kropmans, Kennedy, Stewart, & van Dalen, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Objective structured clinical examinations (OSCEs) are commonly included in health education curricula as they can be used to assess practical skill level and competency through simulation of a real world scenario, but in a mock clinical and examinable setting. Accordingly, OSCEs have been integrated into the curriculum for Bachelor of Nursing programs with other relevant forms of assessment, both internationally and within Australia (Alizadeh et al, 2014;Chiou-Rong & Ue-Lin, 2015;Jo & An, 2014;Mitchell, Henderson, Groves, Dalton, & Nulty, 2009;Setyonugroho, Kropmans, Kennedy, Stewart, & van Dalen, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…One study suggested pre-registration nursing students' felt so stressed by the OSCE and this had a negative impact on their performance (Byrne & Smyth, (2007). While it is recognized that a small amount of stress can enhance performance; adoption of a highly stressful assessment strategy may be counter-productive (Alizadeh et al, 2014;Salehi, Cordero, & Sandi, 2010). Exam-related stress may in part be attributed to a lack of student understanding of, or unfamiliarity with the examination processes and exam requirements (Muldoon, Biesty, Smith, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Empirical evidence indicates an inverse correlation between test anxiety and academic performance in different knowledge domains, such as mathematics (Rana & Mahmood, 2010;Reyes & Castillo, 2015), medicine (Alizadeh et al, 2014;DordiNejad et al, 2011), nursing (Alizadeh et al, 2014;Shapiro, 2014), physics (Rana & Mahmood, 2010), education and languages (Trifoni & Shahini, 2011), statistics (Hunsley, 1985;Rana & Mahmood, 2010), and engineering (Vitasari et al, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Las épocas de exámenes siempre han sido periodos llenos de estrés y preocupación para los estudiantes. La ansiedad que se genera se define como un conjunto de respuestas fenomenológicas, psicológicas, y conductuales que acompañan a preocupación por posibles consecuencias negativas o fracasos en un examen, o situaciones de evaluación similares (Alizadeh et al, 2014), este mismo autor, menciona que la ansiedad ante los exámenes es un tipo común de ansiedad por el desempeño que padecen entre el 10 y el 20 por ciento de los estudiantes.…”
Section: Introductionunclassified